Evaluasi Exposure Index (EI) pada Pemeriksaan Radiografi Thorax Posterior-Anterior (PA): Cross-Sectional Study - Andhika Rizky Tri Nugraha; Gando Sari; Irsal Muhammad; Eka Putra Syarif H; Nurbaiti (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2025)
Chest Posterior-Anterior (PA) radiographic examination is a medical imaging using ionizing radiation to obtain patient diagnostic information. In digital radiographic medical imaging techniques, an indicator shows the radiographic image detector (imaging plate) response to radiation exposure, which is called the exposure index (EI). Therefore, in applying radiation dose optimization in the PA thorax radiographic examination procedure it is necessary to evaluate to determine the indicators of underexposure, optimal exposure, and overexposure exposure. The research method used is quantitative descriptive with cross-sectional study. This research was carried out between March-May 2023 using 70 radiographic examination samples. Then evaluate the percentage of the use of exposure indicators. After that, perform statistical analysis using SPSS IBM25 with Kendall's tau-b test to determine the level of correlation between the use of exposure factors and EI. The results of the study of 70 patients showed an indicator of overexposure of 67% and optimal exposure of 33%. Meanwhile, the results of Kendall's tau-b test showed no correlation between the exposure factor variabel and EI. This shows that using EI as an optimization is not enough to know the exposure factor, but complete radiographic examination procedure data is needed. Keywords: Exposure index, Exposure factor, Chest PA